2017
DOI: 10.1021/jacs.6b11989
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Reaction Process During the S2 → S3 Transition in Photosynthetic Water Oxidation Using Time-Resolved Infrared Spectroscopy

Abstract: Photosynthetic water oxidation performed at the MnCaO cluster in photosystem II plays a crucial role in energy production as electron and proton sources necessary for CO fixation. Molecular oxygen, a byproduct, is a source of the oxygenic atmosphere that sustains life on earth. However, the molecular mechanism of water oxidation is not yet well-understood. In the reaction cycle of intermediates called S states, the S → S transition is particularly important; it consists of multiple processes of electron transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
127
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(157 citation statements)
references
References 72 publications
26
127
3
Order By: Relevance
“…The fast 30-μs kinetic phase is attributed to deprotonation of the cluster, with the slow 350-μs phase representing structural rearrangement, e.g., water insertion and cofactor oxidation. A more recent FTIR study suggests that deprotonation may also occur during the slow 350-μs phase (19). In either case, theoretical calculations support the notion that cofactor oxidation only proceeds via redox tuning (deprotonation) of the cofactor.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The fast 30-μs kinetic phase is attributed to deprotonation of the cluster, with the slow 350-μs phase representing structural rearrangement, e.g., water insertion and cofactor oxidation. A more recent FTIR study suggests that deprotonation may also occur during the slow 350-μs phase (19). In either case, theoretical calculations support the notion that cofactor oxidation only proceeds via redox tuning (deprotonation) of the cofactor.…”
mentioning
confidence: 90%
“…In the next state, S 3 , the net oxidation state of the cofactor is all (Mn IV ) 4 . Electron paramagnetic resonance (EPR) (16), X-ray absorption spectroscopy (XAS) and X-ray emission spectroscopy (XES) (17,18), Fourier transform infrared (FTIR) (19,20), and recent XFEL data (8,21) suggest that in this S state, all 4 Mn ions are octahedral, requiring the insertion of a new water molecule into the cofactor. Structural models of the cofactor in the S 3 state more closely resemble the preceding S 2 A form compared with the S 2 B form, with an additional oxygen (most likely hydroxide) ligand at Mn1 (8,14,16,21) (Fig.…”
mentioning
confidence: 99%
“…The W20 density is already weak in the dark state in comparison to other waters, indicating its higher mobility or lower occupancy. It is likely that the overall changes observed above are a consequence of the oxidation of Mn4 from +3 to +4 in the S 1 to S 2 transition and the connected increase in charge of the cluster (Klauss et al , Sakamoto et al ). Thus, we speculate that the structural changes observed in the W20 region are a consequence of charge compensation around the OEC.…”
Section: Introductionmentioning
confidence: 99%
“…The recent X-ray free electron laser study for the S 3 -state showed the displacement of a water molecule near O4, suggesting the involvement of water molecules near O4 in proton transfer (21). The hydrogen-bond network near Y Z has also been suggested to be a proton pathway (16,17,42,43). Y Z form a hydrogen-bonded triad with D1-His-190 and D1-Asn-298, which is connected with a hydrogen-bond network leading to PsbV through D1-Asn-322 (designated "Y Z -Asn-298 path"; Fig.…”
mentioning
confidence: 99%